PENGGUNAAN MISTERI BOX SEBAGAI MEDIA PEMBELAJARAN IPS DI SEKOLAH DASAR - Winda; Miftahur Rizki; Mutia; Ahmad Suriansyah; Maimunah (STKIP Subang, 2025)
The success of the learning process in education is greatly influenced by various aspects, one of which is the use of learning media. Learning media functions as a means used by teachers to convey material to students effectively through a combination of audio, visual, and audiovisual elements, so that information can be received more interestingly, clearly, and interactively. This research aims to design and develop Misteri Box learning media to increase students' interest in IPAS subjects at SDN Sungai Lumbah 1. This research is motivated by the low interest and understanding of students in learning IPAS, which is caused by learning methods that are still monotonous and do not involve students actively. The approach used is descriptive qualitative with a case study method. Limited trials were conducted on grade IV students at SDN Sungai Lumbah 1, and the results showed an increase in student interest in learning after using the Misteri Box media. This innovation is expected to be one of the alternative learning media solutions that are more fun, interactive, and make it easier for students to understand material about cultural diversity in Indonesia.